PENGARUH PEMBERIAN COGNITIVE BEHAVIOR THERAPY (CBT) TERHADAP PENURUNAN SIMPTOM- SIMPTOM INSOMNIA PADA PENDERITA INSOMNIA - Lenny Syamsudin (LPPM Universitas Muhammadiyah Gorontalo, 2019)
Insomnia is a sleep disorder where a person has difficulty starting sleep, maintaining sleep, or poor sleep quality so that he experiences fatigue, irritability and less productive the next day. In Indonesia the number of people with insomnia is around 30- 50 percent of the total population of Indonesia. This study aims to determine the effect of giving Cognitive Behavior Therapy (CBT) to the reduction of symptoms of insomnia in people with insomnia. The focus of this study is to change the irrational thoughts in people with insomnia, to make it more rational. This research uses Quasi Experiment method with The One Group Pretest-Posttest Design. Insomnia is measured using a measuring instrument that has been adapted from the Pittsburgh Insomnia Rating Scale using the translate re translate method with insomnia subjects. The results showed changes in insomnia characterized by a decrease in insomnia symptoms in the subject after being given an intervention in the form of Cognitive Behavior Therapy (CBT). Based on these data, it can be concluded that the administration of Cognitive Behavior Therapy (CBT) affects the reduction of insomnia symptoms in insomniacsInsomnia merupakan suatu gangguan tidur dimana seseorang mengalami kesulitan untuk memulai tidur, menjaga tidur, atau kualitas tidur yang buruk sehingga mengalami kelelahan, mudah tersinggung dan kurang produktif keesokan harinya. Di Indonesia jumlah penderita insomnia sekitar 30 sampai 50 persen dari total penduduk Indonesia. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian Cognitive Behavior Therapy (CBT) terhadap penurunan simptom- simptom insomnia pada penderita insomnia. Fokus penelitian ini untuk merubah pikiran irasional pada penderita insomnia, agar lebih rasional. Penelitian ini menggunakan metode Quasi Experiment dengan desain The One Group Pretest- Posttest Design. Insomnia diukur dengan menggunakan alat ukur yang telah diadaptasi dari Pittsburgh Insomnia Rating Scale dengan menggunakan metode translate re translate dengan subjek penderita insomnia. Hasil penelitian menunjukkan terjadi perubahan insomnia yang ditandai dengan penurunan simptom-simptom insomnia pada subjek setelah diberikan intervensi berupa Cognitive Behavior Therapy (CBT). Berdasarkan data tersebut, dapat ditarik simpulan bahwa pemberian Cognitive Behavior Therapy (CBT) berpengaruh terhadap penurunan simptom-simptom insomnia pada penderita insomnia.